Birth control campaigns for youths and young adults: From the perspectives of different organizations - Joanne Tay; Alex Vertes; Sabrina Binte Haque; Kun Kan; Elyse Burt; Shannon Sibbald (Cogent Medicine, 2017)
Objectives: To describe the common features of birth control campaigns for youths and young adults, designed by public and private organizations. Methods: Our team conducted a scan for birth control campaigns, through both online resources and bulletin boards. We limited our search to English language birth control campaigns only, those that were released between January 2014 to March 2016, and campaigns that are targeted towards youths. Results: After applying all the limitations, we were left with 11 campaigns. We summarized the content and the communication mode of the campaigns into 4 broad categories: government, non-government, private, and school boards. Birth control campaigns are generally informative and designed to attract the attention of a specific target population. In general, most campaigns are tailored in a culturally appropriate manner to increase community members’ receptiveness towards this topic. Conclusion: Birth control campaigns have been used to disseminate birth control options to youths and young adults. The interactive and personalized campaign quotes were mainly used to help attract target audiences and spread public health messages about the use birth control measures. Future birth control campaigners should consider using these features to help them design and deliver their campaigns.